In an abusive state: how neoliberalism appropriated the feminist movement against sexual violence - Bumiller, Kristin (Duke University Press, 2008)
The sexual violence agenda : feminists and the state -- Gender war : the cultural representation of sexual violence -- Expressive justice : the symbolic function of the gang rape trial -- Administrative injustice : the growth of the therapeutic state -- Victim insurgency : the state as a dangerous stranger -- Universalizing gender justice : at home and abroad